プリンスオラフ カイガン チイキ ノ コウクウ ジキ ソクリョウ - 金子, 英樹; カネコ, ヒデキ; KANEKO, Hideki (国立極地研究所, 1976)
P(論文) The aeromagnetic surveys in the vicinity of Lutzow-Holm Bay, Antarctica, were carried out by the 8th-llth Japanese Antarctic Research Expedition (JARE) during the period from January 1967 to January 1970, for the purpose of investigating the features of the geomagnetic field in the polar region. In succession to these surveys, the aeromagnetic survey of total intensity of geomagnetism in the vicinity of Prince Olav Coast, located northeast of Syowa Station, Lutzow-Holm Bay, was carried out by the 15th JARE during the period of November-December 1974, with a proton precession magnetometer. The observation of total intensity was made at intervals of 6 seconds with unit of 10^γ, and the result was recorded continuously on the analogous recorder. The sensing head was towed by a cable of about 10 m in length from an airplane in order to eliminate the artificial noise during the observation. The flight height was 4,000 ft (1,200 m) and the flight courses covered the space of 100 km in N-S direction by 140 km in E-W direction at intervals of 10 km. The observed values were reduced to the epoch of 28 December 1974. The accuracy of the reduced value, to which all corrections were applied except height correction, is within ±30^γ. The calculated result of the geomagnetic reference field 1975.0, based on IGRF 1965.0 shows that the difference between maximum and minimum values of annual variation in the observed area and its correction for the flight height at 4,000 ft are 8^γ and 24^γ, respectively. From the isomagnetic chart thus obtained, considerably large negative and positive local anomalies in comparison with the reference field are found in the areas off Flattunga and off Hinode Point, respectively. Many small anomalies are also found in the inland area. departmental bulletin paper